Effects of lay support for pregnant women with social risk factors on infant development and maternal psychological health at 12 months postpartum - Popo, Emma (PLoS One, 2017)
BACKGROUND: The ELSIPS (Evaluation of Lay Support in Pregnant Women with Social Risk) RCT showed that lay support for women with social risk had a positive effect on maternal mental health and mother-infant bonding. This exploratory study examined whether these observed benefits would impact infant development at 1 year. METHODS: A sub-sample of women whose infants were under one year who had participated in the ELSIPS RCT which randomised women to receive either standard care or the services of a Pregnancy Outreach Worker (POW), and who were contactable, were eligible to participate in the follow up. At home visits, the Bayley Scales of Infant Development (3(rd) Edition) and standardised measures of depression, self efficacy, mind-mindedness and bonding were completed. RESULTS: 486 women were eligible for follow up, of whom 154 agreed to participate. 61/273 were successfully followed up in the standard maternity care arm and 51/213 in the POW arm. Women who completed follow up were less depressed and had higher selfefficacy scores at 8–12 weeks postpartum than those who did not complete follow up. There were no significant differences in maternal outcomes, infant cognitive development, receptive communication, expressive communication, fine motor development or social/emotional functioning between groups at 12 month follow up. Infants of mothers who received the POW intervention had significantly better gross motor development than infants whose mothers received standard care (p<0.03). CONCLUSIONS: The provision of lay support to women with social risk may facilitate infant gross motor skill development at one year but there were no other demonstrable benefits. The effects of the intervention may be underestimated given that those women who completed follow up had better mental health than the original study sample. TRIAL REGISTRATION: Controlled-Trials.com ISRCTN35027323.